An exploratory study of the prevalence and correlates of student maltreatment by teachers in Cameroon. (15th February 2021) - Benbenishty, Rami; Daru, Etta Roland; Astor, Ron Avi
Abstract: Maltreatment of children takes place in many contexts and places around the world. Based on the model of Bullying, School Violence and Climate in Evolving Contexts, this study describes the prevalence and characteristics of maltreatment of students by their teachers in Cameroon. It examined the bivariate and multivariate correlations between victimization by educational staff with victimization by peers, school climate, and the students' perpetration of violence against their own teachers. The sample consisted of 601 students in three schools. Of these, 62% were females, 63.3% were 13‒16 years old, and 28.8% 17‒20 years old. The study is based on self‐report questionnaires administered to the students. The findings show high levels of student maltreatment—physical, emotional, and sexual. Prevalence was higher among males. These reports were highly correlated with both victimization by peers and student perpetration against teachers. School climate perceptions were negatively associated with staff maltreatment. The discussion notes that the high prevalence of staff maltreatment in this study is similar to findings in developing countries and is higher than in other contexts. Implications and recommendations for policy changes, training, and intervention are presented.